PERAN PEMANDU LOKAL DALAM MENINGKATKAN KEPUASAN WISATAWAN DI DESA PENGLIPURAN, BALI - Syah Fira Ayuningtyas; Eka Putri Nurmayasari; Mulya Nur Aini; Tanziila; Masetya Mukti (Jurnal Kajian dan Terapan Pariwisata, 2026)
Penglipuran Traditional Village, a cultural tourism icon in Bali, is widely recognized for its commitment to environmental cleanliness and the preservation of traditional values. This study aims to examine in depth the contribution of local guides in enhancing visitor satisfaction. A mixed method approach was employed, combining both quantitative and qualitative analyses. Data collection techniques included field observations and the distribution of questionnaires to 62 respondents. The findings indicate that aspects such as information delivery, service ethics, communication skills, and the creativity of local guides received predominantly positive responses. The majority of respondents rated these aspects as "Good" to "Excellent", indicating a high level of tourist satisfaction with the services provided. Practically, the results highlight the importance of improving communication capabilities and developing innovations in technology-based information delivery. The study concludes that local guides play a vital role as facilitators of authentic and satisfying tourist experiences, as well as agents of cultural preservation within the context of a tourism village.